Screening of Lactobacillus from Noi chicken gut as potential probiotics against poultry pathogens - NGUYEN PHUONG THUY; NGUYEN NGOC TRAI (Society for Indonesian Biodiversity, 2024)
Abstract. Thuy NP, Trai NN. 2024. Screening of Lactobacillus from Noi chicken gut as potential probiotics against poultry pathogens. Biodiversitas 25: 3943-3952. This research investigated the potential of Lactobacillus strains isolated from Noi chickens as probiotics for poultry health. We focused on their ability to combat major poultry pathogens: Escherichia coli, Staphylococcus aureus, and Salmonella sp. Thirty-two distinct Lactobacillus strains were successfully cultured from the digestive tracts of Noi chickens. Colony and cell morphology were diverse, confirming the presence of various Lactobacillus species. Biochemical tests further validated their identification. Antibacterial activity screening revealed two strains, LN11 and LN19, capable of inhibiting all three target pathogens. Thirteen isolates, LN5, LN7, LN8, LN9, LN10, LN11, LN12, LN13, LN14, LN16, LN17, LN18, LN19, LN21, LN26 displayed resistance to all four tested antibiotics: chloramphenicol, erythromycin, ampicillin, and ciprofloxacin. Key probiotic traits were assessed. Nine strains showed excellent acid tolerance, crucial for surviving the stomach's harsh environment. Ten strains demonstrated high tolerance to bile salts, essential for thriving in the intestine. LN19 exhibited particularly strong activity, highlighting its potential for probiotic development. Molecular identification using 16S rRNA gene sequencing confirmed the promising isolate LN19 as Lactobacillus farciminis LN19. This study provides valuable insights into the probiotic potential of Lactobacillus strains from Noi chickens. The identification of L. farciminis LN19 with strong antibacterial activity and robust probiotic characteristics suggests its promise for enhancing poultry health and combating infectious diseases.